Spectral mechanical investigation of the elastic interface between a MoS2/graphene heterostructure and a soft substrate. (February 2023) - Xing, Huadan; Wang, Xiaojie; Xu, Chaochen; Du, Hongzhi; Li, Rubing; Zhao, Zihao; Qiu, Wei
Abstract: The interfacial mechanical behaviors of two-dimensional materials and their heterostructures with different substrates are still critical problems in various fields. In this work, a MoS2 /graphene heterostructure was assembled on a formvar/polydimethylsiloxane (PDMS) substrate. Spectral mechanical experiments were conducted via Raman and photoluminescence spectroscopy under equiaxial loading to obtain the strain state of graphene and MoS2 . The experimental results showed that the codeformation assumption, applied as a basic rule in most relative work, was incorrect. This assumption proposed that the substrate and two-dimensional material shared the same strain before interface slip. However, the experiments showed that the strain of the two-dimensional material was much less than that of the flexible substrate and that the former maintained a fixed proportion with the latter. Based on this phenomenon, a strain transfer model of the finitely elastic interface was presented to redefine the interfacial behaviors, and the strain transfer coefficient was introduced to qualify the strain transfer efficiency before interfacial slipping. Finally, a competition mechanism was proposed based on the model to explain the interfacial behaviors of the heterostructure and substrate. Graphical abstract: Image 1 Highlights: Strains of MoS2 /graphene/PDMS structure were characterized by Raman and PL spectroscopy under biaxial tensile loading. Strain transfer model of finitely elastic interface was presented to redefine the interfacial strain transfer mechanism. Strain transfer coefficient was introduced, hence a competition mechanism of heterostructure interface was proposed.